Sensitifitas Kurikulum 2013 : Stigma Sosial dan Positifisme Pemerintah - Halimatus Suhailah (FONDATIA, 2019)
The industrial revolution marked by the term "Age Now" which is rife over the rapid advances in technology will certainly always bring negative changes to society in general and students in particular. It is characterized by negative behaviors that we often encounter in students who lack morality or morality. The reality is also indisputable because the flow of technology will increasingly develop according to modern times. One effort to filter the heavy behavior of the negative is the world of education, which is expected not only to be able to educate, provide the ability to live better in the future, but also able to improve moral eroded by the flow of negative changes. The 2013 curriculum carried by the government is an effort to realize students who are not only qualified on the cognitive side, but also excel in psychomotor and affective students. But the question is, is this positive view of K-13 able to answer the negative stigma of parents and the problems of teachers in educating students who in fact are born from different cultures, and have been strong based on the selfishness caused by ethnicity and dissent? So, this paper raises the authors of the many problems of teachers about the 2013 Curriculum Scientific Approach with descriptive qualitative research methods through the study of library reseach.